1999
DOI: 10.1295/polymj.31.672
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gas Sensor from Poly(ethylene glycol)-Grafted Carbon Black. Responsibility of Electric Resistance of Poly(ethylene glycol)- Grafted Carbon Black against Humidity and Solvent Vapor

Abstract: Poly(ethylene glycol) (PEG) having different molecular weight was successfully grafted onto carbon black surface by direct condensation of terminal hydroxyl groups of PEG with carboxyl groups on the surface using N,N'dicyclohexylcarbodiimide as a condensing agent. The electric resistance of a composite prepared from PEG and PEGgrafted carbon black drastically increased to 10 3-10 4 times of initial resistance in humidity and vapor of methanol, and ethanol, which are good solvent of PEG, and returned immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…The details of the preparation for the sensor materials, measurements of electric resistance and response analysis are described in our previous papers. [4][5][6][7][8] …”
Section: Sensor Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The details of the preparation for the sensor materials, measurements of electric resistance and response analysis are described in our previous papers. [4][5][6][7][8] …”
Section: Sensor Materialsmentioning
confidence: 99%
“…[4][5][6][7][8] Therefore, the radiation grafting onto carbon black is very effective to achieve the effective grafting onto carbon black having few functional groups, such as conductive carbon black.…”
Section: Irradiation Grafting Of Pe Onto Carbon Black Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] On the other hand, Narkis et al 9 have reported the solvent sensing by use of conductive carbon black/polymer composite. Lews et al 10,11 and Zhang et al [12][13][14][15] have also reported the solvent vapor sensing behavior of carbon black/amorphous polymer composites.…”
mentioning
confidence: 99%